Characterization of municipal solid waste in Malaysia for energy recovery - Khamis, Siti Salwa; Purwanto, Hadi; Rozhan, Alya Naili; Abd. Rahman, Mohamed; Mohd. Salleh, Hamzah (2019)
Municipal solid waste (MSW) generation that grows continuously without proper management become worrying phenomenon. Currently, Malaysia is dependent on landfills with almost 85% of waste collected ending up in dumpsites. In order to propose an alternative for solid waste management plan instead of landfill, and to develop a waste-to-energy (WtE) system, the details study of municipal solid waste (MSW) generated is crucial. This paper presents a proposal for energy recovery to produce RDF by studying the characterization of MSW generated in Malaysia; the physical and chemical properties (proximate and ultimate analysis, calorific value or energy content, and thermal analysis) of the waste components to produce a high-quality RDF. The raw MSW sample consisted of 45% organics and food waste, 13% plastics, 9% papers, and 12% diapers. For raw MSW sample, total moisture content, ash content, volatile matter, and fixed carbon were 14.60%, 7.05%, 69.35% and 9% respectively. Gross calorific value is 4538 kcal/kg and carbon content are 45%. The optimum produced RDF sample was found at operating temperature 400°C with total moisture content, ash content, volatile matter, and fixed carbon were 0.75%, 21.65%, 48.35% and 29.22% respectively. Gross calorific value is 6600.15 kcal/kg and carbon content are 64%.